Дослідження неолітичної стоянки Романків 1 на Київщині - Переврзєв, С.В.; Сорокун, А.А. (Кам’яна доба України, 2010)
У статті розглядаються попередні результати дослідження у 2009 році відомої неолітичної пам’ятки Романків 1, що південніше Києва. Article represents preliminary results of investigation of Romankiv 1 site in 2009. D. Telegin’ conclusion about presence of two layers at the site was confirmed in course of excavations. Characteristic features of flint and ceramic assemblages allow to affiliate this site with Kiev-Cherkasy variant of Dnieper-Donetsk cultural-historical area and to date it somewhere between the end of VIth and beginning of Vth millennium BC (cal). Certain Bug-Dniester figurative elements were recovered on Romankiv pottery. This data and peculiarities of flint tool-kit appoints the role of Bug-Dniester population in the process of development of Neolithic in the Middle Dnieper area. Flint assemblage of Romankiv is homogeneous, in spite of variability of ceramic assemblages. These points make the author to confirm the thesis that ceramic is less reliable base for the cultural identification of Neolithic sites then flint tools. The analysis of flint complex proves wrongness of calculation of the ceramic by the general number founded artifacts. The author also makes doubt the reasonableness of calculation of ceramic complex by the structure pastry.